J. B. Priestley, artiste de propagande à la radio : au service de quelles idées ? - Cécile Vallée (Revue LISA)
J.B Priestley’s Sunday Postscript, broadcast on the Home Service of the BBC every Sunday evening from June to October 1940, was one of the major propaganda programmes of the period. Priestley’s adeptness at putting government propaganda into broadcasting terms and sustaining morale on the Home Front was paradoxically accompanied by a controversial political “indiscipline”. His galvanising propaganda consisted in praising the qualities of the ordinary citizen, painting an idealised picture of the “soldiers” on the home Front and of their fight, in promoting the values for which they were fighting and, at the same time, demonising the Nazi enemy, but it sometimes verged on subversive political ideology. His obvious attempts at propagating the vision of a New Jerusalem with its socialist innuendoes were judged as going against the war effort and against national unity. Indeed, the fight against capitalism and the creation of a new world order were not exactly part of the government’s agenda. Notwithstanding, there is another, more philosophical, dimension to Priestley’s 1940 Postscripts which must not be neglected: that of the beauty of the English countryside, and the wonder such beauty should inspire. The Postscripts are also a eulogy to humour, joy, and human relationships, as well as to the community spirit and the continuity of English history, a eulogy to art and knowledge, philosophy and humanities, and, last but not least, to poetry and the power of emotions. Priestley’s artful mixture of poetical and political fervour was an undeniable source of inspiration for the listeners of 1940 and his Postscripts remain to this day in people’s hearts and minds. In the following pages we shall try to analyse their contents, with a view to making a distinction between what is clearly government propaganda and what is Priestley’s own philosophy of life and ideology.